Potential effect of recombinant thrombomodulin on ischemia–reperfusion liver injury in rats. Issue 5 (8th January 2018) - Kimura, Koichi; Yoshizumi, Tomoharu; Inokuchi, Shoichi; Itoh, Shinji; Motomura, Takashi; Mano, Yohei; Toshima, Takeo; Harada, Noboru; Harimoto, Norifumi; Ikegami, Toru; Soejima, Yuji; Maehara, Yoshihiko
Abstract : Aim: Liver ischemia–reperfusion (I/R) injury is a severe complication of liver surgery. However, the responsible molecular mechanism remains unclear. High‐mobility group box 1 (HMGB1) is released from the nuclei of cells and behaves as a damage‐associated molecular pattern. The aim of this study is to reveal the roles of HMGB1 and the effects of recombinant thrombomodulin (rTM) in I/R liver injury. Methods: Rats underwent partial hepatic ischemia followed by reperfusion, and changes in HMGB1 were assessed. Recombinant thrombomodulin was used as an inhibitor of HMGB1. Results: In rats with I/R injury, the HMGB1 level significantly decreased in the liver tissue and significantly increased in the serum after surgery ( P  < 0.001 for both). No difference in the HMGB1 level in the hepatocytes was observed between the rTM(−) group and rTM(+) group after surgery. Conversely, the serum HMGB1 level was significantly lower in the rTM(+) group than the rTM(−) group after surgery ( P  < 0.001). The levels of tumor necrosis factor‐α and interleukin‐6 in the liver tissue 24 h after surgery were significantly lower in the rTM(+) group than the rTM(−) group ( P  < 0.001). The plasma alanine aminotransferase level at 24 h after surgery of the rTM(+) group was significantly decreased after surgery compared with that of the rTM(−) group ( P  < 0.001). The necrotic area of the liver tissue 24 h after surgery was significantly smaller in the rTM(+) group than the rTM(−) group ( P  < 0.001). Conclusions: Recombinant thrombomodulin can serve as a treatment for I/R liver injury by inhibiting HMGB1.